Tasmi’ Al-Qur’an di Kalangan Mahasiswa: - Annisa Nurfauziah; Dadan Rusmana (Jurnal Dirosah Islamiyah, 2023)
This study aims to discuss sima'an especially Sima'an at the Tahfidz Alif Islamic Boarding School. The method used in this research is qualitative in nature with library research, namely finding sources from written materials with a historical approach. The results of the discussion of this study include the understanding and history of Islamic boarding schools in Indonesia, the meaning of sima'an, and the function of implementing sima'an in Islamic boarding schools. This study concludes that sima'an al-Qur'an at the Tahfidz Alif Islamic boarding school has been going on since the establishment of the pesantren in 2009. The background of the students comes from different universities and different faculties. Sima'an for students of the Tahfidz Alif Islamic Boarding School has a religious function which can be seen from the position of the Qur'an for Muslims themselves as a guide or guideline for Muslims to carry out their religious activities. However, as much as 10.3% of students did not feel that sima'an motivated them to become hafidzah. Keywords: tasmi Al-Qur'an, students